The influence of nanotechnology on sports - Li, Y.-J.; Wu, C.-Y. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction At present, nanotechnology is the formation of functional materials, devices, equipments, and systems through control of composition on the nanometer (1 to 100+ nm) length scale and the exploitation of the unique properties and phenomena developed at that scale. A scientific and technical revolution has begun that is based upon the ability to organize and manipulate the matter systematically on the nanometer length scale. Nanotechnology will lead to several industrial revolutions in the 21st century. Nowadays, a number of countries have been devoting to the application of nanotechnology. The purpose of this study is to analyze nanotechnology applications and the influence toward sports development. Methods The research is utilized document analysis method to dissect publications by Taiwan (central) government and related industries. Besides, interviews also have been adopted from relevant policy makers and executives. Results The major findings of this study were as follows: (1) Nanotechnology has been applying to sports medicine, sportswear, sports equipment, and sports architecture. (2) In sports medicine, the nanoscale components have very high surface areas, making them ideal and good for use in composite materials, reacting systems, drug delivery, and energy storage. (3) In sportswear, sports equipment, and architecture, the finite size of material entities, as compared to the molecular scale, determine an increase of the relative importance of surface tension and local electromagnetic effects that make nanostructured materials harder and less brittle. (4) Furthermore, nanotechnology will have practical application to sports media, sports therapy, sports injury, first aid, sports law, sports physiology, sports threpsology, sports biochemistry, and anti-doping and so on. At present, the integration between nanotechnology and sports area is still under way. Discussion / Conclusions Nanotechnology will affect many aspects of our life over next ten to fifteen years [1]. The currently existing multibillion-dollar world market influenced by nanotechnology is supposed to affect nearly any industry sector in the future. As such, the researchers and practioners in sports science are suggested to the Prepare for the future of nanoscience and nanotechnology. It is urgent to provide the scientific basis for nanomaterials performance and integration, and a national resource for training a new generation of searchers in nanoscience and nanotechnology [2]. With all the types about nanotechnology now swirling around any places throughout the world, there is clearly a need to distinguish seriously among product, vision and dream, even in sports area. In order to grasp latest trends in nanotechnology; indeed, the sports should play the active role to join the enormous benefits of nanotechnology and share the global benefits. The researchers expect that these explorations will provide some critical ideas in the academic field and government`s institutions in the future.